Geographical Information System for Indonesian Tourist Destinations - John JOI Ihalauw; Natalia Kristiani Tandafatu (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2021)
Geographical Information Systems have been widely used as a method for effective, efficient and robust decision making in the business world. It has also been used in the selection of precise and accurate tourist destinations. This paper discusses a review of geographical information system for Indonesian tourist destinations. Articles taken from sources in the form of national journals, international journals and conferences proceedings. The author limits the years 2018-2021. Furthermore, the writer will present the taxonomy and summary of the review results. Finally, the authors present research opportunities that have the potential to be studied in the future.